Relationship between fetal-type posterior cerebral artery and basilar artery atherosclerosis - Lijuan Zheng; Lijuan Zheng; Yaozhang Chen; Xin Lin; Shasha Deng; Bin Sun; Bin Sun; Jinmei Zheng; Jinmei Zheng; Fang Zeng; Fang Zeng; Yunjing Xue; et al. (Frontiers in Neurology)
ObjectiveTo investigate the relationship between the morphology of posterior cerebral artery (PCA) and the basilar artery (BA) atherosclerosis disease based on the High-Resolution Magnetic Resonance Vessel Wall Imaging (HR-MRI).MethodsA total of 321 patients presented with cerebrovascular symptoms (posterior circulation ischemic stroke or transient ischemic attack <2 weeks) at the Department of Neurology were collected from July 2017 to June 2020. We systematically collected clinical information, encompassing demographics, medical histories (smoking, alcohol consumption, diabetes, hypertension, hyperlipidemia, and coronary heart disease), and relevant mediation histories. BA curvature, mean lumen area, mean normalized wall index and the morphology of PCA were accessed with HR-MRI and magnetic resonance angiography. The binary logistic regression analysis was used to identify the risk factors of BA plaque formation. Spearman’s bivariate method and correlation coefficients were calculated to analyze the correlations between the morphology of PCA and BA plaque burden. The relationship between different PCA morphologies and posterior circulation infarction was analyzed by Chi square test.ResultsHypertension, diabetes and fetal-type posterior cerebral artery (FTP) were independent risk factors for BA plaque formation in Walking and Lambda geometry subtypes (p < 0.05). For the parameters of BA plaque burden, the PCA morphological type was positively correlated with Mean NWI (r = 0.252, p = 0.03), and that was negatively correlated with mean lumen area (r = −0.35, p = 0.002) and mean vessel area (r = −0.275, p = 0.018) in Lambda subtype. The incidence rate of posterior circulation infarction was statistically significant among different PCA morphologies (p = 0.018).ConclusionFTP was a risk factor of BA plaque formation and it was correlated with BA burden, and which could be used to explain the posterior circulation infarction in patients with FTP.